2023
DOI: 10.1177/09544062231151542
|View full text |Cite
|
Sign up to set email alerts
|

The effects of particle shape on inertial focusing

Abstract: This paper proposes a 2D particle inertial focusing model by the immersed boundary–lattice Boltzmann method (IB-LBM), aiming to study the effects of particle shapes on their focusing state. First, as the validation, we investigated the inertial focusing of circular particles and got consistent focus positions with other previous reports. Then, the inertial focusing of the circle, rectangle, ellipse, and capsule particles were studied in detail. The results revealed that the particle shapes significantly influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Single particle simulations have been used to understand the effect of particle shape on inertial migration. Several works have investigated channel flows with non-circular particles in 2D [114,[135][136][137][138] and non-spherical particles in 3D [70,139,140]. Investigations of rigid biconcave objects have shown that their tumbling rotation leads to an oscillation of the lateral positions that depends on the particle size and aspect ratio [135].…”
Section: Fundamental Migration Dynamics Prohm and Starkmentioning
confidence: 99%
“…Single particle simulations have been used to understand the effect of particle shape on inertial migration. Several works have investigated channel flows with non-circular particles in 2D [114,[135][136][137][138] and non-spherical particles in 3D [70,139,140]. Investigations of rigid biconcave objects have shown that their tumbling rotation leads to an oscillation of the lateral positions that depends on the particle size and aspect ratio [135].…”
Section: Fundamental Migration Dynamics Prohm and Starkmentioning
confidence: 99%